Bortezomib-induced peripheral neuropathy: from molecular mechanisms to clinical management - Yan, Yuting; Song, Yanqi; Zhang, Quan; Hu, Lingwei; Wang, Aidi; Guo, Honglei; Wang, Zhen; Ma, Lin; Liu, Baoshan (Frontiers in Pharmacology, 2025)
Bortezomib (BTZ) is a first-generation proteasome inhibitor that has shown significant efficacy in the treatment of multiple myeloma (MM), providing significant therapeutic benefits without severely compromising overall patient health. However, one of the most common and debilitating side effects associated with BTZ therapy is bortezomib-induced peripheral neuropathy (BIPN). This condition is the leading complication observed in patients undergoing BTZ treatment and has a profound impact on treatment regimens, often necessitating dose reductions or alterations in the dosing schedule. Despite the widespread recognition of BIPN, therapeutic options remain limited. Consequently, further exploration of the molecular mechanisms underlying BIPN is crucial to identify potential therapeutic targets. Establishing standardized, effective treatment strategies is also essential to improve patient outcomes. This review seeks to provide an in-depth overview of the current research on BIPN, covering its clinical presentation, potential pathophysiological mechanisms, and emerging therapeutic strategies. The aim is to offer valuable insights to support the development of novel therapeutic approaches and enhance clinical management of this challenging side effect.